INVESTIGATION OF GROUND PENETRATING RADAR FOR DETECTION OF ROAD SUBSIDENCE NORTHCOAST OF JAKARTA, INDONESIA - Kris Budiono; Yogi Noviadi (Marine Geological Institute of Indonesia, 2012)
A survey of Ground Penetrating Radar (GPR) was conducted in the coastal zone of northern part of Jakarta, Indonesia. The purpose of this survey was to provide the subsurface of coastal Quaternary sedimentary features and stratigraphy disturbances associated with induce post road subsidence 2009. The possibility of subsurface lithology disturbance shown by the GPR record. This record resulted from GPR methods using SIR system 20 GSSI, 270 MHz and 400 MHz and MLF 3200 transducer. The method is a promising tool for resolving changes of physical properties in subsurface lithology condition at the natural scale due to composition changes of physical properties.The reflection data resulted that GPR can distinguish between image the basic geometry forms such as lithology , structure geology , soil and subsurface utilities condition Keywords: Quaternary geology, Jakarta subsidence northern road 2009, Ground Penetrating Radar Penyelidikan â€œGround Penerating Radarâ€ (GPR) telah dilaksanakan di kawasan pantai utara Jakarta Utara, Indonesia. Tujuan dari penyelidikan GPR ini adalah untuk melihat kondisi sedimen Kuarter bawah permukaan dan gangguan stratigrafi sehubungan dengan penurunan jalan raya pada tahun 2009. Kemungkinan gangguan terhadap litologi bawah permukaan terlihat pada rekaman GPR. Hasil rekaman metoda GPR mempergunakan model SIR 20 GSSI, transduser 270MHz, 400 MHz dan MLF 3200.Metoda GPR merupakan alat bantu yang cukup menjanjikan untuk melihat perubahan sifat fisik litologi bawah permukaan pada skala sebenarnya yang disebabkan oleh perubahan komposisi sifat fisiknya. Hasil refleksi data GPR dapat membedakan bentuk dasar geometri seperti litologi, struktur geologi, kondisi utilitas bawah permukaan. Kata kunci : Geologi Kuarter, Penurunan jalan utara Jakarta 2009, Ground Penetrating Radar